Research of Misaligned Load Distribution of Involute Spline Pair based on Finite Element Method - Tan Yuanqiang; Hu Jianfa; Jiang Shengqiang; Yang Shiping; Hu Congfang (Jixie chuandong)
In theoretically,all teeth of spline pair transmitted the same load. In practice,due to manufacturing and mounting errors,not all teeth transmit the same load and as a result,the overloading condition may occur. Based on finite element method,the distribution of contact pressure and load among teeth of involute spline pair with the conditions of angular misalignment,parallel misalignment and those two combined misalignment are investigated. The results have certain guiding significance and engineering application value in guiding involute spline pair manufacturing and assembly.